The Mamfe Basin in the southern Benue trough extension between Cameroon and Nigeria: Gem origin and problem of litho-stratigraphic nomenclature and marine transgression - Tchouatcha, Milan Stafford; Tamfuh Azinwi, Primus; Sobdjou Kemteu, Christel; Balla Ondoa, Augustin Desire; Ngantchu, Leopold Darlus; Azeh Anong, Basil; Gabvourta, Courage (Acta geochimica, 2023)
The Mamfe Basin has been the subject of many studies, but some debates persist, especially concerning the stratigraphic nomenclature, corundum origin, and marine transgression. The aims of this work are (1) to propose a new lithostratigraphic nomenclature of the Mamfe Basin formation based on new field observations, (2) to determine the source rock distribution and the origin of gem deposits and (3) to correlate the Cameroon section of the Mamfe Basin with the Nigerian deposits. The main results show that the name Manyu River Group is more appropriate as the Manyu River crosses all the facies in the Mamfe sedimentary Basin belonging to the Manyu Division. According to the facies analysis, the age of deposition, the mineralogic and geochemical data such as the V vs. Al 2 O 3 and ∑REE vs. Al 2 O 3 , TiO 2 MgO, Na 2 O, P 2 O 5 , and CaO diagrams, this Group is composed of at least five Formations, including four Cretaceous Formations, from bottom to top: the Etoko Formation (alluvial and fluvial channel to fluvio-lacustrine deposits), the Nfaitok Formation (lagoonal deposits), the Bachuo Ntai Formation (fluvial braided channels or fluvio-deltaic environment) and the Eyumojock/Nsanaragati Formation (fluvio-lacustrine deposits) and the new Cenozoic Formation named Bakebe Formation (fluvio-lacustrine deposits). The gem minerals such as corundum, rutile, or tourmaline in the Cretaceous deposits of the Mamfe Basin are mainly detrital as indicated by the presence of worn shapes and fragments of these minerals. The presence of sapphire in the Albo-Cenomanian deposits indicates a Precambrian age of the felsic source rock, likely the plutonic rocks such as granite or pegmatite as indicated by the abundance of tourmaline and high LREE/HREE ratios (14.81–34.29) and slightly negative and positive Eu anomalies (0.85–1.15). This marine incursion in the Mamfe Basin was probably from West Nigeria, according to the geographic location of the Mamfe Basin and the general palaeogeographic evolution of the Benue Trough.